ҚАРАҚАЛПАҚ НАҚЫЛ-МАҚАЛЛАРЫНДА УАҚЫТ ҲӘМ КЕҢИСЛИК МӘСЕЛЕЛЕРИ - Зинатдинова, Г.И. (FAN va JAMIYAT, 2022)
The article deals with the problem of chronotope (time and space) in the Karakalpak folk proverbs. In organizing this problem, attention is focused on such factors as ethnic point of view, worldview, attitude to nature.